Factors influencing seed set in triploid Musa spp. L. - Ortíz, R.; Vuylsteke, D.R. (1995)
Seed set in triploid Musa spp. L. is very low due to high levels of sterility. This makes cross breeding of plantain and banana difficult. Nonetheless, several triploid plantain and banana cultivars produce seeds after hand pollination with diploid parents. This paper reports results about the pattern of seed variation, success of in vitro germination and hybrid production after triploid-diploid crosses. Between-and within-clones differences in seed set were observed. ABB cooking bananas had the highest rates of seed production followed by AAB French plantains. Plantains produced more diploid than tetraploid offsprings after triploid-diploid crosses, which suggests that meiosis resulted in the production of balanced haploid gametes (n = x) due to normal chromosome behaviour between homologous genomes. Seed set variation within clones was influenced by both the production of 2n (= 3x) gametes in the triploid parent and climatic factors. Indeed, seed production, embryo and seed germination success, and euploid and tetraploid hybrid production followed a pattern of seasonal variation reaching a peak in September. High frequency of seed with tetraploid embryos was obtained in the period from January to mid-March. The results demonstrate that production of desirable tetraploids would be more efficient when hand pollinations are done under high temperature, high solar radiation and low relative humidity. These seem to be the most convenient conditions for relatively high production of 2n eggs as compared to haploid gametes.